2014
DOI: 10.18632/oncotarget.2454
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of long non-coding RNAs in human breast cancer clinical subtypes

Abstract: Accumulating evidence highlights the potential role of long non-coding RNAs (lncRNAs) as biomarkers and therapeutic targets in solid tumors. However, the role of lncRNA expression in human breast cancer biology, prognosis and molecular classification remains unknown. Herein, we established the lncRNA profile of 658 infiltrating ductal carcinomas of the breast from The Cancer Genome Atlas project. We found lncRNA expression to correlate with the gene expression and chromatin landscape of human mammary epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
168
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(180 citation statements)
references
References 40 publications
11
168
0
Order By: Relevance
“…HOTAIRM1 may affect cell fate by regulating cell cycle progression and serving as a link in the coordinated regulation of an extensive gene expression program. Although, the expression of HOTAIRM1 was previously shown to be specific to the myeloid lineage of hematopoietic cells (72), a recent study reported that the HOTAIRM1 was overexpressed in the basal-like subtype of breast cancer (73). Together with our present study in PDAC tissues by microarray and qRT-PCR, the long intergenic noncoding RNA HOTAIRM1 may participate in the development and progression of several cancers.…”
Section: Discussionsupporting
confidence: 66%
“…HOTAIRM1 may affect cell fate by regulating cell cycle progression and serving as a link in the coordinated regulation of an extensive gene expression program. Although, the expression of HOTAIRM1 was previously shown to be specific to the myeloid lineage of hematopoietic cells (72), a recent study reported that the HOTAIRM1 was overexpressed in the basal-like subtype of breast cancer (73). Together with our present study in PDAC tissues by microarray and qRT-PCR, the long intergenic noncoding RNA HOTAIRM1 may participate in the development and progression of several cancers.…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, lncRNAs are potential therapeutic targets, and inhibition or overexpression of tumor-specific lncRNAs might have therapeutic implications in TNBC patients (24,25). Recent studies identified several lncRNAs in tight connection with breast cancer (26,27). Su and colleagues (26) divided breast cancer into four different subtypes using lncRNAs data from The Cancer Genome Atlas (TCGA) database and revealed a cluster that was highly correlated with basal-like breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of the function of selected lncRNAs upregulated (19) and downregulated (5) (Su et al 2014). HOTAIRM1 SOX9 is a stem cell factor involved in tamoxifen resistant BCa (Jeselsohn, et al 2017).…”
Section: Lncrnas In Breast Tumorsmentioning
confidence: 99%